Cleaning mums and brave policemen: gender representation and gender-inclusive language in EFL teaching materials in Lithuania - Klein, Annika (Taikomoji kalbotyra, 2019)
Gender representation in textbooks used for teaching English as a foreign or second language (EFL/ESL) has been analysed extensively and in various countries since the 1980s. According to most studies (e.g. Hellinger 1980; Porreca 1984; Ansary and Babaji 2003; Pihlaja 2007; Lee 2016), females tend to be underrepresented and depicted in stereotypical ways, which risks reinforcing gender clichés in students (Britton and Lumpkin 1977; Peterson and Lach 1990). To date, only a few studies (Brusokaitė and Verikaitė-Gaigalienė 2015) have focused on gender representation in teaching materials used in Lithuania; moreover, teaching materials other than textbooks remain underexplored. Using corpus analysis tools and criteria adapted from previous analyses of gender representation and language use in textbooks, this study takes a both quantitative and qualitative approach to the analysis of two EFL exercise books and two EFL test books published in Lithuania between 2005 and 2017 and currently available on the Lithuanian book market. More precisely, areas of investigation were the numerical visibility of males and females, stereotypical contexts in which characters appear, and strategies used by the authors to make the language more gender-inclusive. The results show that males are more visible numerically: not only are there more male than female characters in all four books, males are also more likely to be named first in paired constructions. With regard to stereotypical contexts, both males and females tend to be represented in traditional gender roles: males are typically represented as leaders, the breadwinners of the family and the main decision-makers; females, on the other hand, are depicted as working in stereotypically female professions or in the home domain, and they are more often described as weak, fearful and in need of assistance. Moreover, there is very little variation with regard to the traditional image of a family, typically consisting of a mother, a father and two to three children. As for the use of gender-inclusive language, the use of certain (e.g. naming both male and female pronouns when referring to a person of unknown gender), yet not all available strategies (e.g. singular they) could be observed. These findings suggest that the authors were heavily influenced by the strategies that exist for the Lithuanian language. The language used in the four books can, therefore, be said to differ to some extent from both actual language use (Pauwels 2001; Romaine 2001; Baker 2010) and the language used in teaching materials employed in countries where English is spoken as a first or second language (Jacobs 1999). Finally, this article recommends authors of future teaching materials to pay more attention to the representation of males and females and to also give importance to deviation from what is generally seen as the norm. Arguably, this would provide children with a more truthful picture of contemporary British and North American societies, and help to teach them that diversity is a positive feature.